2016
DOI: 10.1111/mec.13723
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable life history polymorphism may be evolving under divergent selection in the silverleaf sunflower

Abstract: Substantial intraspecific variation in life history is rare and potentially a signal of incipient ecological speciation, if variation is driven by geographically heterogenous natural selection. We present the first report of extensive life history polymorphism in Helianthus argophyllus, the silverleaf sunflower, and examine evidence for its evolution by divergent selection. In 18 populations sampled from across the species range and grown in a common garden, most quantitative traits covaried such that individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 77 publications
3
18
0
Order By: Relevance
“…Although we did not formally measure biomass production, the lower number 511 of tillers and higher amount and size of grains in the highlands when compared with 512 the lowlands may reflect trade-offs between allocation to grain production and 513 24 vegetative growth [84]. Because grains fell at maturity and a single teosinte individual 514 produces hundreds of ears, we were unable to provide a proxy for total grain 515 production.…”
Section: Syndrome Of Adaptation To Altitude 439mentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not formally measure biomass production, the lower number 511 of tillers and higher amount and size of grains in the highlands when compared with 512 the lowlands may reflect trade-offs between allocation to grain production and 513 24 vegetative growth [84]. Because grains fell at maturity and a single teosinte individual 514 produces hundreds of ears, we were unable to provide a proxy for total grain 515 production.…”
Section: Syndrome Of Adaptation To Altitude 439mentioning
confidence: 99%
“…Comparisons of the quantitative genetic divergence of a trait (Q st ) with the neutral genetic differentiation (F st ) can provide hints on whether trait divergence is driven by spatially-divergent selection [17][18][19][20]. Application of these approaches reveals striking examples of divergent selection for developmental rate in the common toad [21], for drought and frost tolerance in alpine populations of the European 90 silver fir [22], and for traits related to plant phenology, size and floral display among populations of Helianthus species [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of the quantitative genetic divergence of a trait (Q ST ) with the neutral genetic differentiation (F ST ) can provide hints on whether trait divergence is driven by spatially-divergent selection [17][18][19][20]. Striking examples of divergent selection include developmental rate in the common toad [21], drought and frost tolerance in alpine populations of the European silver fir [22], and traits related to plant phenology, size and floral display among populations of Helianthus species [23,24]. These studies have reported covariation of physiological, morphological and/or life-history traits across environmental gradients which collectively define adaptive syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this method allows one to compare the level of phenotypic differentiation (Q st ) to the genetic differentiation (F st ) expected under the neutral model of population divergence. In plants, this has been used to investigate the role of selection at the origin of between-populations phenotypic differences related to resource-use traits (Brouillette et al 2014), drought resistance (Ramírez-Valiente et al 2018), life history traits (Moyers and Rieseberg 2016), and functional adaptation to an elevation gradient (Luo et al 2015).…”
Section: Introductionmentioning
confidence: 99%